Bisakah Vlogger Membantu Membangun Kesadaran Merek?Dampak Vlogger Pada Sikap Pelanggan Terhadap Merek Iklan dan Pembelian - Ade Yusi Pamukas; Sumar (Jurnal Manajemen Bisnis Eka Prasetya, 2024)
This research departs from the large number of social media users as a means for carrying out marketing activities. And it also aims to explore the impact of vloggers on customer interest in the products being marketed. Specifically, this research examines whether attitudes towards vlogger recommendations have an impact on attitudes towards brand advertising, and what effect it has on consumer purchasing intentions. This research applies a mono cross-sectional quantitative analysis method. Data collection was assisted using surveys through questionnaires distributed to predetermined samples. Vloggers have quite a big impact on customer perceptions because of their closeness to customers who often describe vloggers as friends and respect their opinions. This study shows that what is important is not the benefits they provide. felt from the information obtained from the vlog. The strongest relationship in this research is attitudes towards vloggers and attitudes towards brands which emphasize content creators in building brand awareness. This article provides a clear picture of the exploration of the impact of vloggers on customer perceptions.